Romantic Marks and Measures : Wordsworth's Poetry in Fields of Print. - Carlson, Julia S. (Material texts., 2016)
In Romantic Marks and Measures, Julia S. Carlson examines Wordsworth's poetry of ""speech"" and ""nature"" as a poetry of print, written and read in the midst of topographic and typographic experimentation and change.